How to draw planes - Bergin, Mark , 1961- (How to draw, 2006)
Offers a practical approach to drawing. This title helps you learn how to draw a variety of planes, from easy aviation to supersonic flying machines. It includes background information on the subject being drawn. It covers a comprehensive range of popular subjects, with sections on material, composition, perspective and technique.